2019
DOI: 10.1002/cbic.201800785
|View full text |Cite
|
Sign up to set email alerts
|

Electronic and Steric Control of n→π* Interactions: Stabilization of the α‐Helix Conformation without a Hydrogen Bond

Abstract: The preferred conformations of peptides and proteins are dependent on local interactions that bias the conformational ensemble. The n→π* interaction between consecutive carbonyls promotes compact conformations, including the α‐helix and polyproline II helix. In order to further understand the n→π* interaction and to develop methods to promote defined conformational preferences through acyl N‐capping motifs, a series of peptides was synthesized in which the electronic and steric properties of the acyl group wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 29 publications
(53 citation statements)
references
References 40 publications
5
48
0
Order By: Relevance
“…The nitrobenzoate group promotes crystal formation in compounds. Within 4 R ‐substituted hydroxyproline nitrobenzoates, we previously observed that the electronic properties of the acyl capping group dramatically impacted the ϕ and ψ torsion angles and n→π* interaction intercarbonyl distances, consistent with stronger n→π* interactions with more electron‐rich acyl donor carbonyls . Therefore, crystallization was attempted on all compounds, in order to identify the inherent conformational effects of 4 S ‐substituted nitrobenzoates and to examine the ability of acyl donor groups to modulate the conformational preferences.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…The nitrobenzoate group promotes crystal formation in compounds. Within 4 R ‐substituted hydroxyproline nitrobenzoates, we previously observed that the electronic properties of the acyl capping group dramatically impacted the ϕ and ψ torsion angles and n→π* interaction intercarbonyl distances, consistent with stronger n→π* interactions with more electron‐rich acyl donor carbonyls . Therefore, crystallization was attempted on all compounds, in order to identify the inherent conformational effects of 4 S ‐substituted nitrobenzoates and to examine the ability of acyl donor groups to modulate the conformational preferences.…”
Section: Resultssupporting
confidence: 80%
“…[4] We previously demonstrated that the interaction strength of an n!p*i nteraction could be modulated by the identity of acyl capping groups that change the electronic properties of the donorc arbonyl. [5] These experiments were conducted using the 4R-nitrobenzoate ester of hydroxyproline, which strongly promotes an exo ring pucker and thus promotes conformationsw ith af avorable n!p*i nteraction. [6] The observed conformations of 4-substituted prolines are dependent on the stereochemistry and the balance of the electronic versus steric effects of the 4-substituent.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Zondlo and co‐workers as well as Reddy et al. have demonstrated through NMR spectroscopy and quantum chemistry calculations of acyl N ‐cap proline derivatives that preferences toward a defined conformation can be modulated through steric and electronic control of the n→π* interactions by varying the bulkiness of the acyl substitution present there . Blackwell and co‐workers have also reported that n→π* interaction and steric repulsion can regulate the cis / trans isomerization ratios of peptoid oligomers .…”
Section: Introductionmentioning
confidence: 99%
“…In principle, the effect of substitution, specially at the n→π* donor (i.e., C=O group), is three‐fold. Substitution of the electron‐donating group (EDG) on the n→π* donor increases the strength of the n→π* interaction by increasing the electron density over the carbonyl oxygen atom while the electron‐withdrawing group (EWG) on the n→π* donor decreases the strength of this interaction by pulling the electron density away from the carbonyl oxygen atom . The substituent on the n→π* donor can also introduce steric repulsion in one of the conformers by rendering conformational preference of the other.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation